ANALISIS PENGARUH BRAND LOYALTY, BRAND IMAGE, IKLAN DAN PERCEIVED QUALITY TERHADAP MINAT BELI KONSUMEN XL PRABAYAR DI KOTA SURABAYA - DWI KURNIAWAN, SAVERIUS (Universitas Katolik Widya Mandala Surabaya, 2012)
The purpose of this research is analysing the impact of brand loyalty, brand image, advertising and perceived quality to the XL prabayar consumers purchase intention in Surabaya. In this research, predicted that those four variables could measure the purchase intention of XL prabayar consumers in Surabaya. This research uses multiple linear regression analysis with 150 respondents using XL prabayar in Surabaya. The sampling technique used was purposive sampling, with the criteria of at least 20 years of age because at that age are considered adults and can make a decisions, at least the respondents used XL prabayar for the past year. This research found that brand loyalty, brand image and percevied quality affects the purchase intention of XL prabayar consumers but the advertising of XL prabayar has no affect to the purchase intention of XL prabayar consumers in Surabaya.